STABILITY ANALYSIS OF AN ECOLOGICAL SYSTEM CONSISTING OF A PREDATOR AND STAGE STRUCTURED PREY - Naji, Raid; Majeed, Azhar (Iraqi Journal of Science, 2024)
In this paper, a mathematical model, consists from a predator interacting with stagestructured prey, is proposed and analyzed. The existence, uniqueness andboundedness of the solution of the proposed model are discussed. The existence andthe stability analyses of all possible equilibrium points are studied. The globalstability of these equilibrium points are performed with suitable Lyapunovfunctions. Finally, the dynamical behavior of the model is investigated numerically.